PENGARUH MODEL PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS TEKS BERITA - Isti Sitihindun; Willyana, Willyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
There were several reasons for conducting this study, students’ seriousness in attending writing news text were still low and not excited. Therefore, the teacher must choose and apply an effective teaching learning model to improve students’ abilities in writing news text. This study aims to improve students’ abilities in writing news text through picture and picture model and investigated students’ responses through teaching writing news text by using picture and picture. The experiment is the research method of this study. The control and experiment class were given pre-test and post-test to know the students’ abilities before and after treatment. The questionnaire also used to gain the data about students’ responses through teaching writing news text by using picture and picture. The research finding shows that the picture and picture model is effective to improve students’ ability in writing news text. The indicators of the success are that: (1) the mean of pre-test result in the experiment class was 48.71, meanwhile the mean of post-test result was 69.03; (2) the students’ responses through questionnaires found that the application picture and picture model was very positive.